IDENTIFICATION OF THE MOTIVE PATTERN OF THE SIKKA SCABBARD USING THE GRAY LEVEL CO-OCCURRENCE MATRIX (GLCM) AND SUPPORT VECTOR MACHINE (SVM) - Dua Reja, Imelda; Alfan, Hilarius; Yunita, Maria (INFOKUM, 2022)
Sikka -Flores Ikat fabrics are part from product culture traditional the Indonesian nation was made for used as clothing for the Sikka people. The development of Sikka's sarong motifs is very variety however not yet once applied use method computing like Support Vector Machine (SVM) for classification and the previous one will do extraction use method Gray Level Co-occurrence Matrix (GLCM) for get information level accuracy classification image of Sikka 's sarong motif.